If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ab + -2b = 0 Solving 2ab + -2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 2ab + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 2ab + 0 = 0 + 2b 2ab = 0 + 2b Remove the zero: 2ab = 2b Divide each side by '2b'. a = 1 Simplifying a = 1
| 2/3x=7/84 | | 4t+3=-21 | | 3/8=9/x | | 5x-2x+3=17x+9 | | 3/4=m/6 | | -x-5=x+9 | | 35+6w=60+4w | | 36f=6 | | 4g+2g+2=26 | | bsquared+12b=bsquared+14b+12 | | 6w^2+25w+14=0 | | (x+0.3)(x+2.2)=0 | | -6h+5=17 | | 7w-4=-18 | | g^2-7g+12=0 | | (-2x+2y-5)=8 | | 11=2-3z | | 0.5*(x+7)+x=15.5 | | -18x-(8x-7)=67 | | 3t^3+30t^2+48t=0 | | -11x-10=x | | F(x)=7lnx | | Y-32=65 | | r+(-3)=8 | | 3/4(5x-4)=13 | | 4/20=120 | | 6=5x+24 | | 4/5*1/16 | | (-2x+-2y+-5)=15 | | 11=18+3z+4z | | 2x^2+2x=576 | | 35/21=45/y |